2022
DOI: 10.1111/pde.14933
|View full text |Cite
|
Sign up to set email alerts
|

Worsening ulceration of infantile hemangioma after initiation or escalation of propranolol

Abstract: For infantile hemangiomas (IH) requiring treatment, including those in high-risk locations or in the setting of ulceration, oral propranolol is first-line therapy. Here, we present three cases of infantile hemangioma with worsening ulceration following initiation or escalation of oral propranolol at standard doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…These have been reported in different contexts, including IH with refractory ulcerations requiring multimodal therapy, worsening of ulceration in segmental IH following initiation or dose escalation of systemic beta-blockers, and persistent or recalcitrant ulcerations in facial segmental IH in patients with PHACE syndrome. [4][5][6] Our study revealed two distinct clinical phenotypes of IH with AU. First, diaper area IH with AU are nearly always segmental with a The contribution of each of these factors to the development of ulceration likely varies and is unique to each IH.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…These have been reported in different contexts, including IH with refractory ulcerations requiring multimodal therapy, worsening of ulceration in segmental IH following initiation or dose escalation of systemic beta-blockers, and persistent or recalcitrant ulcerations in facial segmental IH in patients with PHACE syndrome. [4][5][6] Our study revealed two distinct clinical phenotypes of IH with AU. First, diaper area IH with AU are nearly always segmental with a The contribution of each of these factors to the development of ulceration likely varies and is unique to each IH.…”
Section: Discussionmentioning
confidence: 62%
“…Severe and recalcitrant ulcerations are a well‐recognized challenge in managing patients with IH, yet detailed reports on the subset of patients with AU are sparse and limited to case reports and small case series. These have been reported in different contexts, including IH with refractory ulcerations requiring multimodal therapy, worsening of ulceration in segmental IH following initiation or dose escalation of systemic beta‐blockers, and persistent or recalcitrant ulcerations in facial segmental IH in patients with PHACE syndrome 4–6 …”
Section: Discussionmentioning
confidence: 99%
“…Recent cases in the literature have reported worsening ulceration of infantile hemangiomas after initiation or escalation of propranolol. 18,19 Our secondary analysis of accelerated propranolol initiation dosing in the setting of infantile hemangiomas with active ulcerations or at high risk of ulcerating demonstrated that accelerated initiation of propranolol at the 2 mg/kg/day dose did not demonstrate any increase in the incidence of new or worsening ulceration when compared to the 1 mg/kg/day dose. Additionally, while there was a longer treatment duration for the 1 mg/kg/day group compared to the 2 mg/kg/day group, this difference was not significant.…”
Section: Discussionmentioning
confidence: 86%
“…Lower and more frequent dosing of propranolol (e.g., 1 mg/kg/day TID) has been suggested to prevent paradoxical exacerbation in IH cases with existent or impending ulceration. 2 In severe cases, adjunctive treatment with short-term low-dose oral prednisolone (1 mg/kg/day), as well as pulsed dye laser, can also be beneficial. 3 Finally, complex and refractory cases may benefit from surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Wound care with barrier ointments and dressing placement, when feasible, is essential. Lower and more frequent dosing of propranolol (e.g., 1 mg/kg/day TID) has been suggested to prevent paradoxical exacerbation in IH cases with existent or impending ulceration 2 . In severe cases, adjunctive treatment with short‐term low‐dose oral prednisolone (1 mg/kg/day), as well as pulsed dye laser, can also be beneficial 3 .…”
Section: Discussionmentioning
confidence: 99%